Analisis Kinerja Satuan Polisi Pamong Praja (Satpol PP) dalam Penertiban Pedagang Kaki Lima (PKL) di Jalan Jendral Ahmad Yani Pasar Badak Kabupaten Pandeglang - Andrea Ferruzi Nugraha; Rahmawati Rahmawati; Juliannes Cadith (Journal on Education, 2023)
This study aims to determine the performance of Satpol PP in controlling street vendors (PKL) on Jalan Jendral Ahmad Yani Badak Market, Pandeglang Regency. This research will be conducted using a case study approach, with a descriptive method. This approach will be used to study intensively the background of the Satpol PP performance in controlling street vendors (PKL) on Jalan Jendral Ahmad Yani Badak Market, Pandeglang Regency. The results of the research on the performance of Satpol PP in controlling street vendors (PKL) on Jalan Jendral Ahmad Yani Badak Market in Pandeglang Regency to discipline and make the street vendors (PKL) comfortable in Pandeglang Regency are considered not optimal. Thus, the performance of the Civil Service Police Unit (Satpol PP) of Pandeglang Regency in controlling street vendors (PKL) must be further improved.